2003
DOI: 10.1097/01.asn.0000077347.27669.5c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Common Risk Haplotype for Diabetic Nephropathy at the Protein Kinase C-β1 (PRKCB1) Gene Locus

Abstract: Abstract. Abnormal activation of protein kinase C-␤ isoforms in the diabetic state has been implicated in the development of diabetic nephropathy. It is thus plausible that DNA sequence differences in the protein kinase C-␤1 gene (PRKCB1), which encodes both ␤I and ␤II isoforms, may influence susceptibility to nephropathy. Nine single-nucleotide polymorphisms (SNP) in PRKCB1 were tested for association with diabetic nephropathy in type I diabetes mellitus, by using both case-control and family-study designs. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
3
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 29 publications
4
30
3
1
Order By: Relevance
“…In our previous study (8), a T-G haplotype consisting of two single nucleotide polymorphisms (Ϫ1504C/T and Ϫ546C/G) in the promoter region was associated with twofold increased risk of diabetic nephropathy. Although our report provided the first evidence that the PRKCB1 polymorphisms may contribute to genetic susceptibility to diabetic nephropathy (8), several questions remain unclear: whether this relevance extrapolates to type 2 diabetic subjects, whether the risk haplotype is associated with early diabetic nephropathy, and whether this risk haplotype of PRKCB1 influences kidney function. Therefore, in the present study, we investigated the effect of the risk haplotype of PRKCB1 on diabetic nephropathy by assessing two renal outcomes: transition from any given stage to the more advanced stage of diabetic nephropathy defined by albumin excretion rate (AER) as a time-to-event outcome and kidney function defined by the annual decline rate of estimated glomerular filtration rate (eGFR) as a slope-based outcome.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…In our previous study (8), a T-G haplotype consisting of two single nucleotide polymorphisms (Ϫ1504C/T and Ϫ546C/G) in the promoter region was associated with twofold increased risk of diabetic nephropathy. Although our report provided the first evidence that the PRKCB1 polymorphisms may contribute to genetic susceptibility to diabetic nephropathy (8), several questions remain unclear: whether this relevance extrapolates to type 2 diabetic subjects, whether the risk haplotype is associated with early diabetic nephropathy, and whether this risk haplotype of PRKCB1 influences kidney function. Therefore, in the present study, we investigated the effect of the risk haplotype of PRKCB1 on diabetic nephropathy by assessing two renal outcomes: transition from any given stage to the more advanced stage of diabetic nephropathy defined by albumin excretion rate (AER) as a time-to-event outcome and kidney function defined by the annual decline rate of estimated glomerular filtration rate (eGFR) as a slope-based outcome.…”
mentioning
confidence: 83%
“…Fragments containing the five polymorphic sites in the promoter region of PRKCB1 (Ϫ1504C/T, Ϫ546C/G, Ϫ348A/G, Ϫ278C/T, and Ϫ238C/G) were amplified by the PCR method according to a previously described method (8). Genotyping for all polymorphisms was performed by hybridization with allele-specific oligonucleotide probes (14).…”
Section: Definition Of Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice in which the PRKCB gene was disrupted showed an immunodeficiency. 70 In this context, it is noteworthy that Araki et al 71 recently reported a PRKCB1 association with diabetic nephropathy in type 1 diabetics, a clear autoimmune disease. These findings might link the PRKCB1 gene to both some of the learning inabilities and the immune alterations sometimes seen in autism.…”
Section: Discussionmentioning
confidence: 96%